PENGENALAN SERTA PELATIHAN BAHASA DASAR PEMOGRAMAN WEB (HTML DAN CSS) KEPADA KARANG TARUNA KEL.KEDAUNG KALIANGKE, CENGKARENG, JAKBAR: PENGENALAN SERTA PELATIHAN BAHASA DASAR PEMOGRAMAN WEB (HTML DAN CSS) KEPADA KARANG TARUNA KEL.KEDAUNG KALIANGKE, CENGKARENG, JAKBAR - Ricky Nur Oktavianto; Abdul Jalil2; Antomy Amsyah3; Bagas Dwi Julianto; Deni Sya’ad Ramdhani; Eddion Pratama Saputra; Egi Kurnianto; Fulki Subhan; Muhammad Virzy Ardiansyah; Ricky Nur Oktavianto10 (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The implementation of these activities and learning is related to the application of the benefits of internet science and technology. Through this community service activity, it is targeted to provide benefits for Children or Youth. The provision of learning insights and knowledge carried out by students is to build Wise Children or Youth in using and utilizing the Internet by providing materials and discussions. The training activities contain knowledge or learning materials, application and examples, and questions and answers.